Relation between TLR4/NF‐κB signaling pathway activation by 27‐hydroxycholesterol and 4‐hydroxynonenal, and atherosclerotic plaque instability. Issue 4 (10th March 2015) - Gargiulo, Simona; Gamba, Paola; Testa, Gabriella; Rossin, Daniela; Biasi, Fiorella; Poli, Giuseppe; Leonarduzzi, Gabriella
Summary It is now thought that atherosclerosis, although due to increased plasma lipids, is mainly the consequence of a complicated inflammatory process, with immune responses at the different stages of plaque development. Increasing evidence points to a significant role of Toll‐like receptor 4 (TLR4), a key player in innate immunity, in the pathogenesis of atherosclerosis. This study aimed to determine the effects on TLR4 activation of two reactive oxidized lipids carried by oxidized low‐density lipoproteins, the oxysterol 27‐hydroxycholesterol (27‐OH) and the aldehyde 4‐hydroxynonenal (HNE), both of which accumulate in atherosclerotic plaques and play a key role in the pathogenesis of atherosclerosis. Secondarily, it examined their potential involvement in mediating inflammation and extracellular matrix degradation, the hallmarks of high‐risk atherosclerotic unstable plaques. In human promonocytic U937 cells, both 27‐OH and HNE were found to enhance cell release of IL‐8, IL‐1β, and TNF‐α and to upregulate matrix metalloproteinase‐9 (MMP‐9) via TLR4/NF‐κB‐dependent pathway; these actions may sustain the inflammatory response and matrix degradation that lead to atherosclerotic plaque instability and to their rupture. Using specific antibodies, it was also demonstrated that these inflammatory cytokines increase MMP‐9 upregulation, thus enhancing the release of this matrix‐degrading enzyme by macrophage cells and contributing to plaque instability. These innovative results suggest that, by accumulating in atherosclerotic plaques, the two oxidized lipids may contribute to plaque instability and rupture. They appear to do so by sustaining the release of inflammatory molecules and MMP‐9 by inflammatory and immune cells, for example, macrophages, through activation of TLR4 and its NF‐κB downstream signaling.